Application of Real-time PCR with Mitochondrial D-Loop Specific Primers for Halal Authentication: Identifying Bovine Adulteration in Meatball Products - Arini, Rien Larasati; Rohman, Abdul; Rumiyati (Journal of Food and Pharmaceutical Sciences, 2023)
This study aimed to develop an analytical method using Real-time PCR and a specific primer to analyze bovine DNA in meatballs, addressing the issue of non-halal meat being used in halal meatballs. Real-time PCR enables rapid, specific, and sensitive detection, allowing for qualitative and quantitative identification of species in processed products. The research involved designing specific primers for bovine DNA using IDT software, followed by DNA isolation and testing for various parameters such as specifications, linearity, limit of detection, efficiency, and repeatability. The results demonstrated that the primer D-Loop 922 (forward: 5-ATTACCATGCCGCGTGAA-3', Reverse: 5'-GATGAGATGGCCCTGAAGAAA-3'), designed and tested in silico using Primer-BLAST software from NCBI, effectively identified bovine DNA in both fresh meat and meatballs at an optimum annealing temperature of 59.5°C. The real-time PCR method utilizing the D-loop 922 primer successfully amplified bovine DNA in both bovine samples and bovine meatballs at a minimum concentration of 1 ng, with coefficients of variation (CV) of 0.20% for bovine DNA and 0.22% for bovine meatballs. Consequently, the D-loop 922 primer met the testing criteria and can be utilized to authenticate the halal status of meatball products, supporting the implementation of Law No. 33 of 2014 regarding halal certification.